Pulmonary Hypertension in General Cardiology Practice - Calderaro,Daniela (2019)
Abstract The finding of pulmonary hypertension (PH) by echocardiography is common and of concern. However, echocardiography is just a suggestive and non-diagnostic assessment of PH. When direct involvement of pulmonary circulation is suspected, invasive hemodynamic monitoring is recommended to establish the diagnosis. This assessent provides, in addition to the diagnostic confirmation, the correct identification of the vascular territory predominantly involved (arterial pulmonary or postcapillary). Treatment with specific medication for PH (phosphodiesterase type 5 inhibitors, endothelin receptor antagonists and prostacyclin analogues) has been proven effective in patients with pulmonary arterial hypertension, but its use in patients with PH due to left heart disease can even be damaging. In this review, we discuss the diagnosis criteria, how etiological investigation should be carried out, the clinical classification and, finally, the therapeutic recommendations for PH.